PENGEMBANGAN MEDIA PEMBELAJARAN SEGIEMPAT BERBASIS ADOBE FLASH CS6 MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MEMFASILITASI KEMAMPUAN KONEKSI MATEMATIS - Fera Yuniar; Sumarni Sumarni; Nuranita Adiastuty (Department of Mathematics Education, Universitas Kuningan, 2020)
This type of research is a development or RD which aims to produce a product in the form of quadrilateral learning media based on Adobe Flash CS6 with a valid Contextual Teaching and Learning approach ti facilitate the mathematical connection ability. This study is the research, development model of plomp with consist of three phase is preliminary research, prototyping phase and assessment phase. The instrument used to data collection in this study were questionnaire of epert validation learning media. The device develoved was validated by three validators including two lecture and one teacher junior high school. From the resulting validation data the average score from three validator is 3,4 which means that the learning media is in the valid category with the value obtained is B which means that the learning media can be used with a little revision